Management of dyspnoea in cancer patients - Leppert, Wojciech; Jezierska, Bogna (Medycyna Paliatywna/Palliative Medicine, 2011)
Dyspnoea is one of the most frequent and most burdensome symptoms in patients with cancer, which causes significant deterioration in patients’ activity, well-being and quality of life. The incidence and intensity of dyspnoea increase with the progression of the disease, especially in patients with lung cancer. In this patients’ group lung cancer is often accompanied with chronic obstructive pulmonary disease (COPD) and heart insufficiency, which intensify breathlessness caused by cancer. In this paper epidemiology, causes, assessment, patomechanism and rules of dyspnoea treatment were discussed with the inclusion of the management of the underlying causes and symptomatic treatment.